MENINGKATKAN KEMAMPUAN MEMBACA PUISI MELALUI METODE DEMONSTRASI KELAS VIII DI SMP NEGERI 4 TAPUNG HILIR - Reni Citra Ramadani (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
The purpose of this study is to improve the ability to read Poetry through the demonstration method as Indonesian teaching material in class VIII of SMPN 4. The demonstration method is to provide opportunities for students to translate and apply their knowledge into learning while at the same time giving them an opportunity to demonstrate their level of understanding and mastery of material that has been studied. This research method uses classroom action research methods. The instruments used were test and non-test. The results of the study found that demonstration learning methods can improve the ability to read poetry. Learning achievement increases because of the different learning methods. Students come to the front of the class to read poetry. So that learning activities become more interesting and quality. The results showed an increase in the ability to read poetry of students from the first cycle and second cycle. The results of the first cycle evaluation of 29 students who achieved KKM were 10 students namely 34.48%, and the results of the evaluation of the second cycle value of 29 students who achieved KKM were 24 students namely 82.75%. Suggestions for teachers are needed to use demonstration learning methods so that the learning process becomes more conducive and enjoyable and for parents to pay attention to the activities carried out by children so that they can be controlled and biased to increase achievement.